Pengaruh Motivasi Belajar dan Kecerdasan Emosional Terhadap Hasil Belajar Siswa Kelas Tinggi SD Negeri 01 Nansabaris Padangpariaman - Syafiana Putri, Rati (Lembaga Riset Mutiara Akbar, 2022)
The Influence of Learning Motivation and Emotional Intelligence on Student Learning Outcomes. This study aims to reveal 1) the effect of learning motivation, 2) the effect of emotional intelligence on learning outcomes, and 3) the effect of learning motivation and emotional intelligence on high grade students' learning outcomes on student learning outcomes. This type of research is a correlational study. Sampling in this study used a total sampling technique. Collecting data on learning motivation and emotional intelligence were collected through a questionnaire. The data analysis technique used to test the hypothesis is simple and multiple correlation analysis and significant test using t-test. , t-count>t-table at the 0.05 level of significance. (2) Furthermore, the statistical results of emotional intelligence on learning outcomes are obtained tcount = 5.3 and ttable = 1.67, (3) Then the statistical results for learning motivation and emotional intelligence on learning outcomes are obtained fcount = 20.48 and ftable = 3.32, fcount>ftable. This means that there is an influence of learning motivation and emotional intelligence on student learning outcomes at SD Negeri 01 Nansabaris Padangpariaman